2002
DOI: 10.1088/0022-3727/35/5/307
|View full text |Cite
|
Sign up to set email alerts
|

Optical computerized tomography of the E-H transition in inductively coupled plasmas in Ar and Ar-CF4mixtures

Abstract: We have applied optical emission spectroscopy together with computerized tomography (CT) to study the transition between E and H modes in inductively coupled plasma. Measurements were performed in pure Ar and in CF4(5%)/Ar mixture in the pressure range between 5 and 300 mTorr. It was found that the radial and azimuthal CT images of the E (capacitively coupled) mode are quite different from those of the H (inductively coupled) mode. The E mode structures show clearly the presence of capacitive coupling, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 18 publications
(38 reference statements)
3
36
1
Order By: Relevance
“…The stepped increase in emission intensity and the hysteresis effect above about 50 mTorr ͑6.7 Pa͒ is typical of previously reported E -H transitions and hysteresis in ICPs. 5,7,8 When the plasma power ͑P p ͒ dependence on the applied power ͑P a ͒ is explored ͑not shown͒, it is found that for small applied powers, the rate of increase of P p is much slower than P a until about 25 W, where a discontinuity occurs, P p jumps, and the rate of further increase in P p is similar to that of P a with a slope of nearly one. The discontinuity in the graph occurs in the vicinity of the E -H mode transition and hysteresis seen in the plasma emission measurements ͑Fig.…”
Section: ͑1͒mentioning
confidence: 99%
“…The stepped increase in emission intensity and the hysteresis effect above about 50 mTorr ͑6.7 Pa͒ is typical of previously reported E -H transitions and hysteresis in ICPs. 5,7,8 When the plasma power ͑P p ͒ dependence on the applied power ͑P a ͒ is explored ͑not shown͒, it is found that for small applied powers, the rate of increase of P p is much slower than P a until about 25 W, where a discontinuity occurs, P p jumps, and the rate of further increase in P p is similar to that of P a with a slope of nearly one. The discontinuity in the graph occurs in the vicinity of the E -H mode transition and hysteresis seen in the plasma emission measurements ͑Fig.…”
Section: ͑1͒mentioning
confidence: 99%
“…7 Recently, the effect of a change in the ionization mechanisms of the discharge, between direct ionization from the ground state and stepwise ionization through metastable states, on the mode transitions and the accompanying hysteresis was discussed for argon discharges. [8][9][10] However, the mechanisms behind the mode transitions are still not well understood, and the established models are not yet sophisticated enough to predict the transition behavior in detail. For example, unknown temporal structures in the transition dynamics were observed recently 11 which show that considerable further research is required to fully understand the discharge operation in the mode transition region.…”
mentioning
confidence: 99%
“…(6) and of the ohm resistance in Eq. (8). J s ðrÞ in the sheath width equation indeed varies radially.…”
Section: Capacitive Branchmentioning
confidence: 90%
“…6 As is well known, two discharge modes exist in typical reactors, i.e., the capacitive E mode at low density and the inductive H mode at high density. [7][8][9][10][11][12][13][14] Either continuous or abrupt transitions between the two discharge modes can be triggered by varying the applied power or the matching status of the circuit. We also note that the mode transitions of these bi-stable discharges in ICP and microwave plasmas 15 exhibit hysteresis, and several mechanisms have been proposed to explain the presence of hysteresis, including nonlinear behavior in the plasma and the circuit, the effects of impedance matching, and power loss in the external circuit.…”
Section: Introductionmentioning
confidence: 99%